2013
DOI: 10.5901/ajis.2013.v2n6p23
|View full text |Cite
|
Sign up to set email alerts
|

Role of Social Studies Education in National Development in Nigeria

Abstract: Social Studies Education as a field of study instills in students the knowledge, skills, attitudes and actions that are considered important in the relationship and interaction of man and those around him on one han, and the entire environment (Ogun Bameru, 2006). The paper examines social studies education in the context of Nigeria's philosophical goals as a nation, the objectives of social studies education and how they can be used to achieve national goals and development and proffers some suggestions which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…The study's conclusions support the choices made by Ogun-Bameru (2006) and Ahmad (2013) about social studies as a topic that improves students' knowledge, skills, attitudes, and behaviours. Social studies education is seen as crucial for understanding how people interact and relate to one another as well as to their surroundings.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The study's conclusions support the choices made by Ogun-Bameru (2006) and Ahmad (2013) about social studies as a topic that improves students' knowledge, skills, attitudes, and behaviours. Social studies education is seen as crucial for understanding how people interact and relate to one another as well as to their surroundings.…”
Section: Discussionsupporting
confidence: 78%
“…The results also corroborate those of Njeng'ere (2014), who pointed out that the four pillars of learning to live together, know, do, and be together Social studies promote integration and national cohesion. Education in social studies has been identified as a discipline that helps achieve national goals through citizenship education, claims Ahmad (2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Collaborate with other health personnel in research study relating to substance abuse thus providing new information in the Psychological care of clients with substance abuse [21][22][23][24][25][26][27][28].…”
Section: Nursing Researchmentioning
confidence: 99%
“…Apart from that, it can provide new experiences for students who are too bored with conventional learning models such as the lecture method. IT (Information Technology) based learning media can also increase learning motivation and attract students' attention (Dania, 2015;Abubakar, 2013). The use of IT-based learning media also helps teachers in creating effective and efficient learning.…”
Section: Introductionmentioning
confidence: 99%